Anisotropic paste conductive composite material prepared by blending method and preparation method and application thereof

The anisotropic paste-like conductive composite material prepared by blending method solves the problem of unstable electrical connection of electrophysiological signals on the surface of hairy skin, and realizes the effect of high-quality electrophysiological signals on the rough surface.

CN119463465AActive Publication Date: 2025-02-18SUZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411631574.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

When electrophysiological signal acquisition is performed on the surface of hairy skin, it is difficult to achieve stable electrical connections, which affects the stability and reliability of electrophysiological monitoring equipment.

Method used

Anisotropic paste-like conductive composite material, including polymer matrix material, multi-walled carbon nanotubes and silver nanosheets, is prepared by blending method, to form a reliable conductive network, and improve adhesion and electrophysiological signal acquisition ability.

Benefits of technology

It realizes a stable electrical connection on rough skin or tissue surface for a long time, improves the stability and reliability of electrophysiological monitoring equipment, and ensures high-quality transmission of electrophysiological signals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463465A_ABST
    Figure CN119463465A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of flexible electronic materials, and particularly relates to an anisotropic paste conductive composite material prepared by a blending method and a preparation method and application thereof. The paste conductive composite material is prepared from the following raw material components: a polymer matrix material, a multi-walled carbon nanotube and a silver nanosheet. The polymer matrix material is obtained by heating and reacting polyethylene glycol, polypropylene glycol and polyethylene glycol segmented copolymer, isophorone diisocyanate and a catalyst at 50-70 DEG C for 10-14 hours. The invention also provides a preparation method of the paste electrode material. The paste electrode material can be used for collecting electrophysiological signals on the surfaces of various complex biological tissues, and the problems that in the prior art, due to rough and complex surfaces, the electrophysiological signals are distorted or lost, and hair needs to be removed for detecting the electrophysiological signals in a hairy area are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of flexible electronic materials, and in particular relates to an anisotropic paste-like conductive composite material prepared by a blending method, and a preparation method and application thereof. Background Art

[0002] Electrophysiological signals reflect the state of the human body, and a stable human-machine interface is crucial to improving the precision and accuracy of detecting physiological signals. With the development of flexible sensors, convenient electrophysiological monitoring equipment increasingly requires reliable electrical connections at the human-machine interface. In order to meet the needs of electrophysiological monitoring, a variety of flexible electrodes have been developed. A key feature of these electrodes is the ability to form conformal and seamless contact with animal tissue or skin surfaces. However, this sufficient electrical connection is often difficult to achieve when acquiring electrophysiological signals on hairy skin surfaces, such as head electroencephalogram (EEG) without shaving hair or non-invasive detection of animal signals.

[0003] The main function of using a paste conductive material is to maintain a stable electrical connection for a long time when facing various complex animal tissues or skin surfaces, thereby ensuring that the electrophysiological monitoring equipment can continuously collect accurate electrophysiological signals. The present invention develops a composite paste electrode by mixing a polymer matrix with a conductive nanofiller. The paste electrode can be conformally coated on a smooth or rough surface and has sufficient adhesion and the function of collecting electrophysiological signals. Summary of the invention

[0004] In order to solve the above problems, the purpose of the present invention is to overcome the adverse effects of rough skin or tissue surface morphology on electrophysiological signal acquisition, provide a stable electrical connection for the human-machine interface to improve the stability and reliability of electrophysiological monitoring equipment.

[0005] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:

[0006] The invention provides an anisotropic paste-like conductive composite material prepared by a blending method, comprising a polymer matrix material, multi-walled carbon nanotubes and silver nanosheets; the polymer matrix material is obtained by heating a polyethylene glycol polypropylene glycol polyethylene glycol block copolymer, isophorone diisocyanate (IPDI) and a catalyst at 50-70°C for reaction for 10-14h.

[0007] Polyethylene glycol (PEG)-polypropylene glycol (PEG)-block copolymer was purchased from Sigma-Aldrich with the product number 435465.

[0008] Preferably, the number average molecular weight (Mn) of the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer is 4000-6000.

[0009] Preferably, the catalyst is selected from dibutyltin dilaurate (DBTDL).

[0010] Preferably, the multi-walled carbon nanotubes have a diameter of 10-30 nm and a length of 10-30 μm.

[0011] Preferably, the diameter of the silver nanosheets is 1-5 μm.

[0012] Preferably, the mass ratio of the polymer matrix material, the multi-walled carbon nanotubes and the silver nanosheets is 18-22:0.5-1.5:10-14.

[0013] Preferably, the molar ratio of the polyethylene glycol polypropylene glycol polyethylene glycol block copolymer to isophorone diisocyanate is 1:1 to 1.1:1*10 -4 ~3*10 -4 .

[0014] The present invention also provides a method for preparing the anisotropic paste-like conductive composite material prepared by the blending method, comprising the following steps:

[0015] S11: After dissolving the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer, adding isophorone diisocyanate and a catalyst at room temperature (25±5° C.), heating at 50-70° C. for reaction for 10-14 h to obtain a reaction solution;

[0016] S12: volatilizing the solvent in the reaction solution to obtain a polymer matrix material;

[0017] S13: mixing the polymer matrix material and the multi-walled carbon nanotubes for 160-200 seconds to obtain a mixed material;

[0018] S14: adding silver nanosheets to the mixture, mixing for 160-200 seconds, and then air-drying to obtain the anisotropic paste-like conductive composite material prepared by the blending method.

[0019] Preferably, in the step S11, the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer is purified by vacuum drying at 40° C. for 1-2 hours before dissolving.

[0020] Preferably, in step S11, the dissolving temperature is 60° C. and the dissolving method is stirring.

[0021] Preferably, the polyethylene glycol polypropylene glycol polyethylene glycol block copolymer is dissolved in chloroform, and the mass ratio of chloroform to the polyethylene glycol polypropylene glycol polyethylene glycol block copolymer is 2-4:1.

[0022] The above is a water-washable paste electrode and a preparation method thereof, comprising the following steps: (a) mixing purified poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) and isophorone diisocyanate (IPDI) in a chloroform solvent, and causing a polymerization reaction under the action of a catalyst to obtain a paste-like polymer matrix material; (b) mixing the polymer matrix material with multi-walled carbon nanotubes and silver nanosheets using a planetary mixer and volatilizing excess solvent.

[0023] Specifically, the method for preparing the anisotropic paste-like conductive composite material prepared by the blending method comprises the following steps:

[0024] (1) drying poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) (average Mn is 5800) under vacuum at 40° C. for 1-2 h to obtain purified poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol);

[0025] (2) dissolving the purified poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) in a solvent 3 times its mass, stirring, heating to 60° C. to fully dissolve, and adding isophorone diisocyanate (IPDI) and a catalyst dropwise at room temperature, wherein the molar ratio of the purified poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) to isophorone diisocyanate (IPDI) is 1:1.03, stirring, heating to 60° C. to react for 12 h, cooling, pouring into an evaporating dish, stirring at room temperature in a fume hood for 72 h, and volatilizing the solvent to obtain the component A.

[0026] (3) According to the mass fraction, 20 parts by mass of component A were added into a PE mixing tank (30 mL), and then 1 part by mass of multi-arm carbon nanotubes was added thereto. The mixing tank was then sealed and placed in a planetary mixer for stirring for 180 seconds.

[0027] (4) Open the mixing tank, add 12 parts by weight of silver nanosheets into the mixing tank, seal the mixing tank, place it in a planetary mixer and stir for 180 seconds.

[0028] (5) The evenly mixed composite material is placed in a ventilated environment to dry and can be directly taken out for use.

[0029] The present invention also provides a universal water-washable paste electrode for electrophysiological signal monitoring, comprising the anisotropic paste-like conductive composite material prepared by the blending method.

[0030] The technical solution of the present invention has the following advantages over the prior art:

[0031] The paste-like conductive composite material described in the present invention further polymerizes the polymer material poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) to increase the polymer chain segments and improve the crosslinking degree and viscosity of the polymer matrix material. In addition, a reliable conductive network is constructed by using one-dimensional and two-dimensional nano-conductive fillers, which effectively reduces the amount of nano-fillers used and ensures excellent electrophysiological signal transmission quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a comparison chart of the signal crosstalk between the paste-like composite material of Example 1 and the commercial gel material.

[0033] Figure 2 This is a comparison chart of the adhesion performance of the paste composite material of Example 1, the commercial gel material and the commercial patch electrode.

[0034] Figure 3 This is a photo of the polymer matrix material.

[0035] Figure 4 It is the viscosity curve of the polymer matrix material.

[0036] Figure 5 The figure is a flow chart for preparing anisotropic paste-like conductive composite materials prepared by a blending method.

[0037] Figure 6 The graph of loss modulus and storage modulus of the composite material prepared in Example 1 is shown.

[0038] Figure 7 This is a diagram showing the distribution of conductive fillers in polymer matrix materials. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0040] Example 1

[0041] An anisotropic paste-like conductive composite material is prepared by a blending method, and the steps are as follows:

[0042] (1) drying poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) (average Mn: 5800) at 40° C. in vacuum for 2 h to obtain purified poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol);

[0043] (2) dissolving the purified poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) in 3 times the mass of solvent chloroform, stirring, heating to 60° C. to fully dissolve, and adding isophorone diisocyanate (IPDI) and a catalyst dropwise at room temperature of 25° C., wherein the molar ratio of the purified poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) to isophorone diisocyanate (IPDI) is 1:1.03:2*10 -4 , stirred, heated to 60°C for reaction for 12h, poured into an evaporating dish after cooling, stirred at room temperature for 72h in a fume hood, evaporated the solvent, and obtained a polymer matrix material;

[0044] (3) Add 10g of polymer matrix material to a PE mixing tank (30mL), and then add 0.5g of multi-walled carbon nanotubes. Then seal the mixing tank and place it in a planetary mixer for stirring for 180s; the total mass of the mixer's counterweight system is 500g, the mixer's revolution speed is 1500r / min, and the mixer's rotation speed is 1000r / min;

[0045] (4) opening a mixing tank, adding 6 g of silver nanosheets therein, and then sealing the mixing tank and placing it in a planetary mixer for stirring for 180 s; the total mass of the mixer's counterweight system is 500 g, the mixer's revolution speed is 1500 r / min, and the mixer's rotation speed is 1000 r / min;

[0046] (5) Place the mixed composite material in a fume hood to air dry.

[0047] Example 2

[0048] An anisotropic paste-like conductive composite material is prepared by a blending method, and the steps are as follows:

[0049] (1) drying poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) (average Mn: 5800) at 40° C. in vacuum for 2 h to obtain purified poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol);

[0050] (2) dissolving the purified poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) in 2-4 times the mass of solvent chloroform, stirring, heating to 60° C. to fully dissolve, and adding isophorone diisocyanate (IPDI) and a catalyst dropwise at room temperature of 25° C., wherein the molar ratio of the purified poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) to isophorone diisocyanate (IPDI) is 1:1.03:1*10 -4 , stirred, heated to 50°C for reaction for 10 hours, poured into an evaporating dish after cooling, stirred at room temperature for 72 hours in a fume hood, evaporated the solvent, and obtained a polymer matrix material;

[0051] (3) Add 9g of polymer matrix material to a PE mixing tank, and then add 0.25g of multi-walled carbon nanotubes. The diameter of the multi-walled carbon nanotubes is 10nm and the length is 10μm.

[0052] Then the mixing tank was sealed and placed in a planetary mixer for stirring for 160 seconds; the revolution speed of the mixer was 1500 r / min, and the rotation speed of the mixer was 1000 r / min;

[0053] (4) opening the mixing tank, adding 5 g of silver nanosheets with a sheet diameter of 1 μm, and then sealing the mixing tank and placing it in a planetary mixer for stirring for 180 s; the revolution speed of the mixer is 1500 r / min, and the rotation speed of the mixer is 1000 r / min;

[0054] (5) Place the mixed composite material in a fume hood to air dry.

[0055] Example 3

[0056] An anisotropic paste-like conductive composite material is prepared by a blending method, and the steps are as follows:

[0057] (1) drying poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) (average Mn: 5800) at 40° C. in vacuum for 2 h to obtain purified poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol);

[0058] (2) dissolving the purified poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) in chloroform solvent of 4 times its mass, stirring, heating to 60° C. to fully dissolve, and adding isophorone diisocyanate (IPDI) and a catalyst dropwise at room temperature of 25° C., wherein the molar ratio of the purified poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) to isophorone diisocyanate (IPDI) is 1:1.03:3*10 -4 , stirred, heated to 70°C for reaction for 14h, poured into an evaporating dish after cooling, stirred at room temperature for 72h in a fume hood, evaporated the solvent, and obtained a polymer matrix material;

[0059] (3) Add 11g of polymer matrix material to a PE mixing tank, and then add 0.75g of multi-walled carbon nanotubes. The diameter of the multi-walled carbon nanotubes is 30nm and the length is 30μm.

[0060] Then the mixing tank was sealed and placed in a planetary mixer for stirring for 200 seconds; the revolution speed of the mixer was 1500 r / min, and the rotation speed of the mixer was 1000 r / min;

[0061] (4) opening the mixing tank, adding 7 g of silver nanosheets with a sheet diameter of 5 μm, and then sealing the mixing tank and placing it in a planetary mixer for stirring for 180 s; the revolution speed of the mixer is 1500 r / min, and the rotation speed of the mixer is 1000 r / min;

[0062] (5) Place the mixed composite material in a fume hood to air dry.

[0063] Application Example 1

[0064] Select two points 10 cm apart on the upper arm along the axis of the arm, take out the anisotropic paste-like conductive composite material prepared in Example 1 of the present invention as a paste electrode and evenly apply it to the two selected points, use a thin copper sheet as a receiving electrode to collect human electromyographic signals (EMG) (Note: human electromyographic signals cannot be collected by directly placing a thin copper sheet on the arm), and place the thin copper sheet on the surface of the evenly applied paste electrode to adhere tightly. After collecting and recording the electromyographic signals, rinse with pure water, and then attach commercial electrode patches (purchased from HealForce) to the same two positions to collect electromyographic signals under the same action. After calculation and comparison, the electromyographic signals collected by the two methods have a comparable signal-to-noise ratio.

[0065] Application Example 2

[0066] Without removing hair, the EEG signals at the human head are monitored. Two points (10-20 cm apart) are selected in the area covered with hair, and an appropriate amount of the paste electrode of the present invention is evenly applied to the two selected points. A thin copper sheet is used as the receiving electrode as in Application Example 1, and the thin copper sheet is placed on the paste electrode for connection. After collecting and recording the signal, the applied area is rinsed with clean water to remove it. Similarly, commercial electrode patches are pasted at the two selected points to monitor EEG signals. Without removing any hair, the commercial electrode patches cannot monitor EEG signals of any band.

[0067] Application Example 3

[0068] The performance stability of materials is crucial for long-term monitoring of electrophysiological signals. Compared with the commercial gel with the same function currently available on the market, the paste electrode of the present invention exhibits better long-term stability. Specific comparison measures are as follows:

[0069] (a) The paste electrode material and the commercial gel material were placed in exactly the same environment and their respective mass changes were measured after 24 hours. Due to the water loss of the commercial gel, the mass of the commercial gel decreased to about 10% of the original mass after 24 hours, while the mass of the paste electrode hardly changed.

[0070] (b) The paste electrode material and the commercial gel material were placed in exactly the same environment and their viscosity changes were measured after 24 hours. The commercial gel became solid after 24 hours, while the viscosity of the paste electrode hardly changed.

[0071] Application Example 4

[0072] Signal crosstalk is also an important factor affecting the quality of electrophysiological signal acquisition. The skin impedance is measured using metal electrodes 2 mm apart. The paste electrode and commercial gel material described in the present invention are evenly applied between the electrode and the skin, and then the applied strip copper electrode is attached to the arm skin to measure the human skin impedance. The two materials are applied separately on the two metal electrodes for the first time, and the entire area between the two metal electrodes is evenly applied for the second time (the two metal detection electrodes are connected to each other through the applied paste electrode or commercial gel material). After testing and comparison, it is found that the measured skin impedance is significantly reduced when the commercial gel material is applied as a whole piece, indicating that the signal crosstalk caused by short circuit occurs. However, the paste electrode prepared by the present invention does not show abnormal phenomena.

[0073] In addition, the adhesion performance of the paste electrode material described in the present invention also has obvious advantages over commercial electrode patches and commercial gel materials, which can ensure that the electrophysiological detection port is directly pressed against the paste electrode material described in the present invention without falling off, thereby causing unstable electrophysiological signal output.

[0074] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. An anisotropic paste-like conductive composite material prepared by a blending method, characterized in that: The invention comprises a polymer matrix material, multi-walled carbon nanotubes and silver nanosheets; the polymer matrix material is obtained by heating a polyethylene glycol polypropylene glycol polyethylene glycol block copolymer, isophorone diisocyanate and a catalyst at 50-70°C for reaction for 10-14h.

2. The anisotropic paste-like conductive composite material prepared by the blending method according to claim 1, characterized in that: The number average molecular weight of the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer is 4000-6000.

3. The anisotropic paste-like conductive composite material prepared by the blending method according to claim 1, characterized in that: The catalyst is selected from dibutyltin dilaurate.

4. The anisotropic paste-like conductive composite material prepared by the blending method according to claim 1, characterized in that: The multi-walled carbon nanotubes have a diameter of 10-30 nm and a length of 10-30 μm.

5. The anisotropic paste-like conductive composite material prepared by the blending method according to claim 1, characterized in that: The diameter of the silver nanosheet is 1-5 μm.

6. The anisotropic paste-like conductive composite material prepared by the blending method according to claim 1, characterized in that: The mass ratio of the polymer matrix material, the multi-walled carbon nanotubes and the silver nanosheets is 18-22:0.5-1.5:10-14.

7. The anisotropic paste-like conductive composite material prepared by a blending method as claimed in claim 1, characterized in that: The molar ratio of the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer to isophorone diisocyanate is 1:1-1.

1.

8. A method for preparing the anisotropic paste-like conductive composite material prepared by a blending method according to any one of claims 1 to 7, characterized in that: The steps include: S11: After dissolving the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer, adding isophorone diisocyanate and a catalyst at room temperature, heating at 50-70° C. for reaction for 10-14 hours to obtain a reaction solution; S12: volatilizing the solvent in the reaction solution to obtain a polymer matrix material; S13: mixing the polymer matrix material and the multi-walled carbon nanotubes for 160-200 seconds to obtain a mixed material; S14: adding silver nanosheets to the mixture, mixing for 160-200 seconds, and then air-drying to obtain the anisotropic paste-like conductive composite material prepared by the blending method.

9. The preparation method according to claim 8, characterized in that: The polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer is dissolved in chloroform, and the mass ratio of the chloroform to the polyethylene glycol-polypropylene glycol-polyethylene glycol block copolymer is 2-4:

1.

10. A universal water-washable paste electrode for electrophysiological signal monitoring, characterized in that: The anisotropic paste-like conductive composite material is prepared by a blending method as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Hydrophilicity hot melt type polyurethane contact adhesive and preparation method and use

    CN101418192A

  • Conductive mixed isocyanate polyurethane material and preparation method thereof

    CN110563920A

  • Elastic and stretchable gel polymer electrolyte

    CN111433248A

  • Antibacterial and conductive high-elongation degradable film material and vocal cord sensing application thereof

    CN118165501A

  • Conductive ink

    US20100140564A1